La langue maternelle, une stratégie pour enseigner/apprendre la langue étrangère - Rabéa Benamar (Multilinguales)
The Algerian sociolinguistic situation is characterized by a variety of existing languages. This linguistic diversity led consequently to the emergence of many phenomena (such as borrowing, code-switching, etc.) mainly observed in educational interactions. So, an important question is posed in this article about the position and the role of the mother tongue in French as a foreign language in the Algerian context ; in interactions and interviews with both secondary teachers and students. To this end, we would like to test the idea that the implementation of strategies (the use of mother tongue in particular) is necessary both to mutual understanding and releasing communication in an FFL classroom.